Typification of the name Pteris multifida (Pteridaceae subfamily Pteridoideae) - Mazumdar, Jaideep; Arana, Marcelo D. (Phytotaxa, 2016)
Pteris multifida, sometimes called ‘spider fern’, ‘spider brake’, ‘Chinese brake’, or ‘Huguenot fern’, is characterized by its distal pinnae of mature leaves being simple, adnate and decurrent to the rachis in at least the distal ½ of the leaf, and the venation is entirely free. The species is native to subtropical Asia and was probably first collected from China. The species is commonly cultivated as an ornamental and has become naturalized in many parts of tropical Africa (Verdcourt 2002) and America (Prado & Windisch 2000, Christenhusz 2010, Martínez 2011). It grows terrestrially or epiphytically in moist, open, disturbed places.